STUDIES ON THE FOOD AND FEEDING RELATIONSHIPS OF THE INSHORE FISHES OFF CALICUT ON THE MALABAR COAST - Venkataraman, G (Indian Journal of Fisheries, 2016)
THE importance of the study of the food of fishes with its bearings on thedifferent aspects of their biology like shoaUrig and migratory habits, feedingadaptations, growth, etc., is well known and considerable work has beendone on this subject abroad since the close of the last century. Thoughvery little was known hitherto about the food of fishes in Indian seas, therehas been some addition to our knowledge in recent years. Some of theearlier papers dealing with the subject are on the food of Sardinella longiceps(Hornell and Nayudu, 1924), S. gibbosa (Devanesan, 1932) and perches ofthe Madras coast (Job, 1940). Chidambaram and Venkataraman (1946)and Devanesan and Chidambaram (1948), in their accounts of the marinefood fishes of the west coast and common food fishes of the Madras Presidencyrespectively, have given brief notes about their food. Chacko(1949), in his account of the food and feeding habits of the fishes of Gulfof Mannar, has given a historical resume of the papers pertaining to thefood of fishes in Indian waters pubUshed till then.